Performa Sperma Ikan Nilem (Osteochillus vittatus) Pasca Penyimpanan Terhadap Persentase Fertilitas dan Daya Tetas Telur - Dewi Wisudyanti; Emyliana Listiowati; Anandita Ekasanti; Dewi Nugrayani (Jurnal Airaha, 2021)
The purpose of this study was to determine the effect of adding honey with different concentrations in the extender on the percentage of fertility and hatchability of nilem fish (Osteochillus vittatus) eggs fertilized by stored sperm. This study used a completely randomized design (CRD) with a factorial pattern of 2 x 4 with 4 replications. The type of extender (Factor A) consisted of egg yolk milk and coconut water, while the concentration of honey (Factor B) used was 0%, 3%, 6%, and 9%. Observations on the percentage of fertility and egg hatchability were carried out to determine the sperm performance of nilem fish. Data analysis was carried out statistically using statistical analysis of variance (ANOVA) and further tested using multiple distance tests (Duncan). Data analysis showed that there was an interaction between the two factors that gave a significant effect on the percentage of fertility and egg hatchability. The combination of milk and egg yolk extender with 6% honey concentration gave the highest yield of 61.75% for fertility and 23.08% for temporary hatchability, for the lowest percentage of fertility was 4% for coconut water without honey and the lowest percentage was for hatchability egg yolk milk extender without honey was 7.51%.